“Darius the Great is Not Okay” Guide - Kansas State University, K-State First (Kansas State University, K-State First, 2019)
This guide provides resources for faculty and staff at Kansas State University on the book 2019 common book, "Darius the Great is Not Okay" by Adib Khorram. Included in the guide are discussion questions, suggested classroom activities, other titles of interest, vocabulary, and additional resources.
Citation: K-State First (2019). Darius the Great is Not Okay [Brochure]. Manhattan, Kansas: K-State First.
Keywords: Darius the Great is Not Okay, The; Common reading program; Guide; First-year experience program; Application of learning